Unless As Stone Is - Lohmann, Sam (punctum books, 2014)
The sestina is a form in which words repeat regularly, intricately, appearing and reappearing in new contexts with new meanings. Sam Lohmann's Unless As Stone Is emerged from a few years of living with Dante's sestina, "Al poco giorno e al gran cerchio d'ombra." He allowed the text to appear in its own new - if irregularly scheduled - contexts. New translations, new scenery, new meanings; new phrases entered the poem (from García Lorca, from Sappho, from strangers and from loved ones) and found their own patterns. What resulted is a serial poem in seven movements, incorporating several strategies of reincorporation. "Quandunque i colli fanno più nera ombra" - "All our oddity operates / on changing verity."